Identification of U6 Promoter and Establishment of Gene-Editing System in Larix kaempferi (Lamb.) Carr - Jun-Xia Xing; Ao-Jie Luo; Xin-Hao Wang; Qi Ding; Ling Yang; Wan-Feng Li (Plants)
This study aimed to establish a CRISPR/Cas9 gene-editing system for Larix kaempferi (Lamb.) Carr. (Japanese larch). We screened L. kaempferi U6 promoters and used them to drive sgRNA expression in the CRISPR/Cas9 gene-editing system. The L. kaempferi embryogenic callus was used as the receptor material for genetic transformation, and the frequency and types of gene editing were then analyzed. The results showed various mutations in the transgenic materials, including base substitutions and deletions, and the editing frequency ranged from 5% to 14.29%. In summary, we established a CRISPR/Cas9 gene-editing system for L. kaempferi. Our results demonstrate that the CRISPR/Cas9 system can efficiently edit genes in L. kaempferi, with significantly higher editing frequencies observed when sgRNA expression is driven by endogenous LaU6 promoters compared to the exogenous promoter ProAtU6-26. This work provides technical support for the study of L. kaempferi gene functions and genetic improvement.